Safety of the balloon catheter for cervical ripening in outpatient care: complications during the period from insertion to expulsion of a balloon catheter in the process of labour induction: a systematic review. (10th January 2018) - Diederen, M; Gommers, JSM; Wilkinson, C; Turnbull, D; Mol, BWJ
Abstract : Background: It has been suggested that cervical ripening with a balloon catheter for labour induction can be done in an outpatient setting in low‐risk pregnancies. Introduction of such an approach needs to be accompanied with monitoring of potential complications. Therefore the existence and frequency of any associated adverse event during cervical ripening needs to be established. Objective: To assess the complication rate during cervical ripening with balloon induction. Search strategy: We searched Embase, Medline, Cochrane Collaboration and CINAHL using keywords 'induction of labour', 'cervical ripening', 'balloon catheter', 'Foley balloon', 'transcervical balloon'. Selection criteria: We included randomized controlled trials and cohort studies containing original data on fetal and maternal morbidity in pregnant women during cervical ripening with a balloon catheter. Only articles for which authors were able to give data for this exact time frame were included. Data collection and analysis: Two reviewers assessed independently the eligibility of included studies, extracted data and performed a quality assessment. A meta‐analysis was performed to calculate the estimated prevalence of the adverse events. Main results: In total 26 studies were included reporting on 8292 women. The estimated prevalence of the analysed adverse events in the random effects model was between 0.0 and 0.26%, of which 'pain/discomfort' had the highest prevalence. Conclusion: This study suggests the risk of adverse events during the period between insertion and expulsion of a balloon catheter in cervical ripening to be low. These data facilitate further evaluation and implementation of this procedure in an outpatient setting for low‐risk pregnancies. Tweetable abstract: Balloon catheter for cervical ripening appears to be safe enough to evaluate its use in the outpatient setting. Tweetable abstract: Balloon catheter for cervical ripening appears to be safe enough to evaluate its use in the outpatient setting.